Plasma catecholamines in acute stroke - Kobayashi, Shotai; Tazaki, Yoshiaki; Furuhashi, Norihisa; Hayashi, Hidehito; Kanda, Tadashi (Japanese Journal of Stroke, 1980)
Plasma catecholamines were measured in 19 control subjects and 64 patients with acute stroke, admitted within 48 hours of onset. Plasma norepinephrine (pNE) and epinephrine (pE) were determined by the application of high speed liquid chromatograph combined with trihydroxy indole method. Markedly elevated levels of pNE and pE were observed in patients with massive cerebral hemorrhage and cerebral embolism with large hemispheric infarcts. The levels of pNE gradually decreased over the next few days. The mean pNE values for cerebral hemorrhage, cerebral infarction and subarachnoid hemorrhage within 48 hours of onset were 753±116 pg/ml (SEM), 397±65 pg/ml and 630±291 pg/ml, respectively. The mean value for cerebral hemorrhage was significantly higher than that of 292±29 pg/ml for control subjects (p<0.005) and that for cerebral infarction (p<0.01). The mean value of pE for cerebral hemorrhage was also significantly higher than those for cerebral infarction and control subjects. The mean pNE levels of 1199±162 pg/ml in 13 died patients (11 cerebral hemorrhage, 2 cerebral infarction) were significantly higher than that of 362±39 pg/ml in 43 survived patients (p<0.001), suggesting that the plasma levels of NE within 48 hours of onset well reflect the prognosis. These results indicate that excessive sympathetic nerve discharge occurred concomitantly with adrenomedullary hyperfunction following the onset of stroke.